HUBUNGAN LAMA DUDUK DAN SIKAP DUDUK DENGAN KELUHAN NYERI PUNGGUNG BAWAH (LOW BACK PAIN) PADA PEKERJA PEMOTONG IKAN - Rahmad Gurusinga; Tati Murni KaroKaro; Kardina Hayati; Sarmana .; Bunga Br Saragih (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Low back pain (LBP) is a very common world health problem, which causes activity restrictions and also absenteeism from work. Low back pain can reduce human productivity, 50-80% of workers worldwide have experienced low back pain where almost a third of their age have experienced some type of low back pain which is the second disease after the flu. The purpose of this study was to determine the relationship between sitting and sitting posture with complaints of low back pain among fish cutter workers at UD. Dumbo Jaya Group, Kota Galuh Village, Perbaungan District, Serdang Bedagai Regency. The research method uses an analytical survey with a cross sectional design. The number of samples as many as 31 fish cutter workers, data collection using questionnaires and data analysis using the chi-square test with a significant level of 95% or p?? (0.05). The results showed that there was a significant relationship between length of sitting and complaints of low back pain in fish cutter workers P = 0.013 < = 0.05 and there was a significant relationship between sitting posture and complaints of low back pain in fish cutter workers P = 0.039 < = 0.05. It is recommended for fish cutter workers to be able to arrange rest hours and a good sitting posture so that lower back pain does not occur.